Membangun Generasi Muda yang Takut Akan Tuhan di Era Digital - Karwadi Karwadi; Luki Krispriyanto; Rode Sri Rahayu (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
With the development of the times, the lives of today's young people have a way of getting along and a communication style that is greatly influenced by the environment. In fact, it is also inseparable from the influence of technology which is very rapidly developing in this era, where young people are now more active in using or utilizing the development of technology through communication tools in which there are social media such as mobile phones, laptops, and others that are connected to the internet network. Without having to meet and interact in person, they will get a very extraordinary influencer, which will shape their character to be good or even vice versa. The influence of the development of technology and community has a great influence on the lives and future of young people. Both in general and especially God's children who are lay and those who are involved in the ministry. No less important is when they start thinking about their future with various family backgrounds and their current conditions. Sometimes worries arise about their future, making them do something that seems good, but actually makes them start to move away from God. The author's hope is to create a young generation who fear God.